PEMBERDAYAAN GURU DAN ORANGTUA DALAM UPAYA MENANGKAL LGBT PADA GENERASI MUDA - Mutimatun Ni’ami (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2021)
Indonesia is a country based on God Almighty, the existence of LGBT is contrary to the basic principles of the state. Therefore, efforts to counteract the existence of LGBT must be carried out by all elements, both government and society. Given that LGBT is spread through social media, providing education to teachers and parents is a breakthrough effort so that the dangers can be prevented from an early age. Through this seminar, it is hoped that awareness will arise about the dangers of LGBT and foster a synergy in empowering teachers and parents to prevent itKeywords : God Almighty, empowering, LGBT